Ordovician sponges from the Lenoir Limestone, Tennessee: new evidence for a differential sponge distribution along the margins of Laurentia. (January 2020) - Carrera, Marcelo G.; Sumrall, Colin D.
Abstract: Five genera of anthaspidellid and streptosollenid demosponges are described from the Ordovician Lenoir Limestone near Lenoir City, Loudon County, Tennessee, USA including: Rhopalocoelia regularis Raymond and Okulitch, Rugocoelia loudonensis n. sp., Psarodictyum sp. (Anthaspidellidae), Allosacus pedunculatus n. sp., and Zitelella varians Raymond and Okulitch (Streptosolenidae). These findings confirm the major paleobiogeographic picture for Laurentian sponges (i.e., the differential distribution of sponge faunas along both North American margins), because none of these eastern margin species has been reported from western margin faunas. Only one genus typical of the Great Basin fauna, Rugocoelia Johns, 1994, is reported from Tennessee, but as a new species. Possible explanations are discussed for this differential distribution, mainly related to climatic constraints or sedimentary differences, preventing the free distribution of sponge species between Laurentian continental margins. UUID: http://zoobank.org/2b990a4c-7bc8-4eb6-b8a9-fe4ecf7bdbf9